The factors that influence the awareness of cash waqf among Muslim community in Kuala Terengganu - Ummi Shahirah, Mamat Yusof (2020)
This study is about the awareness of cash waqf among Muslim community in Kuala Terengganu by measuring the following factors: social influence, religious value and financial ability. The Self-Awareness Theory (William, 1985) was used as a basis for this study. A structured question was designed where the data were analysed by using t-test, ANOVA, correlation and multi regression analysis. This paper is an attempt to determine the factors that influence the awareness of cash waqf among Muslim community in Kuala Terengganu by investigating three dimension which are social influence, religious value and financial ability. The aims of this paper are to identify the differences on the demographic factors of (gender, age, educational level, occupation). Secondly, to determine the relationship between social influence, religious value and financial ability towards the awareness of cash waqf among Muslim community in Kuala Terengganu. Last but not least to study the influence of social influences, religious value and financial ability towards awareness of cash waqf among Muslim community in Kuala Terengganu. The targeted population for this study is Kuala Terengganu. The study employed a quantitative type of research using questionnaires and the sample comprised of 380 respondents. The study found two determinants to be significant in influencing the awareness of cash waqf among Muslim community in Kuala Terengganu namely religious value and financial ability. Therefore, this study provided great contributions, implications and has recommended for waqf institutions on how to improve the awareness on cash waqf.